Intersections of the knowledge-power nexus as a precursor to (dis)empowerment and resistance in the poetry of Maya Angelou - Kaberia, Teresia; Ndivo, Larry (International Journal of Research and Scholarly Communication, 2021)
This article investigates how knowledge and its recursive relation with power is manifested in the poetry of Maya Angelou. It analyses how various contexts, such as the social, political, cultural and historical, inform knowledge production and how the Foucauldian concept of the knowledge/power nexus is employed as a strategy of (dis)empowerment and resistance by marginalized persons in her poetry. It also, explores how Angelou’s poetry utilises the female body as the site of the manifestation of the knowledge/power nexus and resistance. The article utilises textual data obtained through critical reading and analysis of poems from The Complete Collected Poetry of Maya Angelou. In its analyses, it makes use of three poems; Men and Phenomenal Woman and Seven Women’s Blessed Assurance. It concludes that the knowledge/power nexus as manifested in her poetry is representative of a vantage point from which one stands empowered to re-examine their social situation and re conceptualize ways in which to subvert domination.
Keywords: empowerment; intersections; knowledge; power; resistance; social context